Generation of Thyroid Follicular Cells from Pluripotent Stem Cells: Potential for Regenerative Medicine - Sewell, Will; Lin, Reigh-Yi (Frontiers in Endocrinology, 2014)
Nearly 12 percent of the population in the United States will be afflicted with a thyroid related disorder during their lifetime. Common treatment approaches are tailored to the specific disorder and include surgery, radioactive iodine ablation, antithyroid drugs, thyroid hormone replacement, external beam radiation, and chemotherapy. Regenerative medicine endeavors to combat disease by replacing or regenerating damaged, diseased or dysfunctional body parts. A series of achievements in pluripotent stem cell research have transformed regenerative medicine in many ways by demonstrating “repair” of a number of body parts in mice, of which, the thyroid has now been inducted into this special group. Seminal work in pluripotent cells, namely embryonic stem cells and induced pluripotent stem cells, have made possible their path to becoming key tools and biological building blocks for cell-based regenerative medicine to combat the gamut of human diseases, including those affecting the thyroid.